Mechanoresponsive Luminescence: Mechanoresponsive Luminescent Molecular Assemblies: An Emerging Class of Materials (Adv. Mater. 6/2016). Issue 6 (5th February 2016) - Sagara, Yoshimitsu; Yamane, Shogo; Mitani, Masato; Weder, Christoph; Kato, Takashi
Abstract : The possibility of changing the molecular assembly of organic and organometallic materials through mechanical stimulation has enabled the design of a growing family of molecular materials with mechanoresponsive luminescence (MRL) characteristics. On page 1073, Y. Sagara, T. Kato, and co‐workers review the state of the field and highlight emerging trends. The cover image shows the MRL behavior of a cyano‐oligo(phenylenevinylene) dye. Image credit: Marc Karman, Adolphe Merkle Institute, University of Fribourg, Switzerland.